“I made friends a lot more easily”: children and families’ experiences of social group programs for children on the autism spectrum - Maya Hayden-Evans; Bahareh Afsharnejad; Elinda Ai Lim Lee; Ben Milbourn; Tanya Picen; Mathew Johnson; Sven Bölte; Sonya Girdler (BMC Pediatrics)
Abstract Background Social Skills Group Programs (SSGP) target the social communication and interaction skills of children on the autism spectrum. This qualitative study explored lived experiences of children and families who participated in a randomised controlled trial (RCT) evaluating the efficacy of KONTAKT™ adapted for younger children (8 to 12 years) in comparison to an active control social art group (ART Legends). Methods Semi-structured interviews were conducted online with parents (n = 37) and children (n = 35) who participated in the RCT, immediately following the interventions. Interview questions were designed to elicit responses relating to program content, structure, and experiences. The data were analysed using a deductive coding framework. Results Findings suggest SSGPs such as KONTAKT™, implementing multiple teaching strategies, and less structured social group activities such as ART Legends can both have a perceived positive influence on outcomes. More children in the KONTAKT™ group reportedly improved their social skills than those in the art group. Overall, participants’ experiences were predominantly positive. Both barriers (e.g., session timing, distance from home) and facilitators (e.g., support of family members) to participation were identified; feelings towards individual aspects of the groups were dependent on a range of personal factors (e.g., existing commitments). Conclusion This study describes experiences of organised social group participation from the perspectives of children on the spectrum and their families, supporting the positive influence of such contexts for autistic youth. Suggestions made by participants to improve social groups are presented, contributing to ongoing development of SSGPs for children on the spectrum. Trial registration (1) Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12619000994189, registered 12 July 2019, anzctr.org.au; (2) ClinicalTrials.gov: NCT04024111 registered 1 December 2019, https://clinicaltrials.gov .